The Approach of Democracy in Islamic Political Thought - Odah, Ramzi (Journal of Humanities & Social Sciences, 2019)
The present study examined the problematic relationship between democracy and the system of government in Islam, whereby considering that the concept of democracy represents a conceptually fundamental dilemma in Islamic political thought due to the link between this concept and secularism, and to the difference of opinion and diligence about it, and as a result of the expansion of the intellectual perspective of Islam as a religion without a state. This study found that there is a great degree - though not comprehensive - in the democratic conception covered by the Islamic political heritage through the inclusion of this heritage on the main dimensions of the theory of democracy in the contemporary sense; these dimensions are social contract, allegiance, Shura, human rights and the separation between the authorities. On the other hand, the study found that there are a number of religious, political, cultural and tribal factors that blended together and led to the exclusion of democracy as an explicit concept in the sources of Islamic political heritage despite the latter's coverage of the dimensions of democracy.
Keywords: democracy; Islam; system of government; politics